2012
DOI: 10.1158/0008-5472.can-12-0877
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Robo1 Signaling of Breast Cancer Cells by Slit2 from Stromal Fibroblast Restrains Tumorigenesis via Blocking PI3K/Akt/β-Catenin Pathway

Abstract: Tumor microenvironment plays a critical role in regulating tumor progression by secreting factors that mediate cancer cell growth. Stromal fibroblasts can promote tumor growth through paracrine factors; however, restraint of malignant carcinoma progression by the microenvironment also has been observed. The mechanisms that underlie this paradox remain unknown. Here, we report that the tumorigenic potential of breast cancer cells is determined by an interaction between the Robo1 receptor and its ligand Slit2, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
111
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(121 citation statements)
references
References 37 publications
7
111
0
Order By: Relevance
“…These observations are in line with existing concepts on how loss of SLIT2 affects tumor progression, which propose that SLIT2 counteracts cell motility induced by chemoattractant stimulation via cytokines or growth factors (36)(37)(38). Different from the SLIT2 mode of action in breast (39) and lung cancer cells (40), we did not detect a SLIT2-dependent regulation of AKT activity in PDAC cells (data not shown), suggesting a cell type-specific wiring of downstream signals.…”
Section: Discussionsupporting
confidence: 91%
“…These observations are in line with existing concepts on how loss of SLIT2 affects tumor progression, which propose that SLIT2 counteracts cell motility induced by chemoattractant stimulation via cytokines or growth factors (36)(37)(38). Different from the SLIT2 mode of action in breast (39) and lung cancer cells (40), we did not detect a SLIT2-dependent regulation of AKT activity in PDAC cells (data not shown), suggesting a cell type-specific wiring of downstream signals.…”
Section: Discussionsupporting
confidence: 91%
“…Also in other tumor entities, e.g. breast and pancreatic cancer, it was recently shown that high Robo1 or Robo2 expression correlated with a more favorable prognosis [22,23]. Furthermore, it was shown that by applying recombinant Robo4 protein angiogenesis and/or tumor growth was inhibited, and vice versa that blocking Robo4 with monoclonal antibodies increased angiogenesis and disrupted vascular integrity [24].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in lung cancer, it was also reported that Slit2/Robo1 signaling suppresses lung cancer progression and that patients with loss of Slit2 had a poor prognosis [32]. Further data supported that inhibition of Robo1 signaling led to metastasis inhibition [31]. …”
Section: Robo Receptors Stabilize the Angiogenic Network Counteractinmentioning
confidence: 97%
“…Also, in other cancer entities, increased expression levels were of prognostic value, as seen in breast and pancreatic cancer [30,31]. Furthermore, in lung cancer, it was also reported that Slit2/Robo1 signaling suppresses lung cancer progression and that patients with loss of Slit2 had a poor prognosis [32].…”
Section: Robo Receptors Stabilize the Angiogenic Network Counteractinmentioning
confidence: 99%